The Synthesis and Application of Functionalized Mesoporous Silica SBA-15 as Heterogeneous Catalyst in Organic Synthesis - Ziarani, Ghodsi M.; Roshankar, Shima; Mohajer, Fatemeh; Badiei, Alireza (Current Organic Chemistry, 2021)
Mesoporous silica nanomaterials provide an extraordinary advantage for making new and superior heterogeneous catalysts because of their surface silanol groups. The functionalized mesoporous SBA-15, such as acidic, basic, BrÖnsted, lewis acid, and chiral catalysts, are used for a wide range of organic syntheses. The importance of the chiral ligands, which were immobilized on the SBA-15, was mentioned in this review to achieve chiral products as valuable target molecules. Herein, their synthesis and application in different organic transformations are reviewed from 2016 till date 2020.
Keywords: lewis acid catalyst